PERKEMBANGAN PENGAWASAN HIGIENITAS MAKANAN DAN MINUMAN DI KOTA CIREBON (1906-1940) - Mutawally, Anwar Firdaus (Balai Pelestarian Nilai Budaya Kalimantan Barat, 2024)
This research aims to explain the development of food and drink hygiene supervision in Cirebon City during the colonial period. The motivation for writing this article stems from the lack of research on food and drink hygiene supervision in the Dutch East Indies, par ticularly in Cirebon City. The study applied a historical method consisting of four stages: heuristics, criticism, interpretation and historiography. The findings indicate that imple menting food and drink hygiene monitoring policies in Cirebon City was prompted by Euro peans' concerns about poor food quality, the influence of ethical politics, efforts to dispel fatalistic attitudes among the local population, and the typhus outbreak in 1913. During that period, the city government made several efforts to improve public health, including enhancing the conditions of slaughterhouses, monitoring food factories (such as hotels, restaurants, and cafes), conducting inspections in traditional markets, and promoting hy giene within the community